Effects of Prolonged Treatment With Co-trimoxazole on the Thyroid Gland, Liver, and Epididymal Sperm Reserve in Dogs - Davinson C Anyogu; Vincent SO Shoyinka; John I Ihedioha (SAGE Publishing, 2017)
Co-trimoxazole is an antimicrobial drug gotten from potentiation of sulfamethoxazole with trimethoprim. It is widely used for the treatment of bacterial and protozoan infections in humans. It is also used in veterinary clinics against susceptible microorganisms, but thyroid dysfunction has raised concern especially in dogs. This study aimed to determine the effects of prolonged treatment with co-trimoxazole in euthyroid dogs. Dogs were given co-trimoxazole at 30, 60, and 120 mg/kg body weight at 12-hour intervals for 21 days. Standard procedures were used to assay total T 4 and T 3 , thyrotropin, testosterone, aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase in serum. The thyroid gland and testes were weighed. In addition, thyroid and liver were examined histologically. Epididymal sperm count was also performed. Co-trimoxazole caused dose-dependent depression of serum thyroxine levels with severe colloid depletion, intrafollicular hemorrhage, hyperplasia, and hypertrophy of the follicular cells. The liver showed vacuolar hepatopathy. Epididymal sperm count was low in the 120 mg/kg-treated group. The study revealed that thyroid hemorrhage and lowered epididymal sperm reserve were new findings in co-trimoxazole toxicity in dogs.